Drug Repurposing and Dosage Form Development of Anti-COVID-19 - Kwok, Kevin (Pharmaceutical Sciences and Research, 2021)
The COVID-19 pandemic has been occurring approximately for more than 1 year. This pandemic has been a health issue that hits all countries in the world caused by the transmission of SARS-CoV-2 virus from one individual to another. The symptoms showed from the infected are fever, shortness of breath, dry cough, headache, and sore throat, among others. The SARS-CoV-2 virus is transmitted through sneezing, coughing, talking, and touching infected objects. Along with this transmission, the SARS-CoV-2 virus will continue to mutate. This mutation becomes an obstacle as well as a challenge to find drugs that can overcome the SARS-CoV-2 virus effectively and safely. The drugs used as anti-COVID-19 are still limited. The steps taken in the process of discovering and developing anti-COVID-19 drugs were through the drug repurposing approach because of the advantages it provides, such as shortens the duration and minimizes the costs required. After several drugs that have potential as anti-COVID-19 were obtained, further research on the development of dosage forms and formulas was carried out to obtain more effective and safer anti-COVID-19 drugs. This review aims to discuss several drugs gained from drug repurposing that have the potential as anti-COVID-19 drugs such as remdesivir, chloroquine/hydroxychloroquine, azithromycin, corticosteroids, and other potential drugs. This review will also discuss several developments of dosage form from the repurposed drugs.